2005
DOI: 10.1128/jcm.43.1.376-381.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of High-Risk Human Papillomavirus (HPV) between Parents and Infant: a Prospective Study of HPV in Families in Finland

Abstract: The Finnish HPV Family Study is a prospective cohort study assessing the dynamics of human papillomavirus (HPV) transmission between parents and infant. Serial genital and oral scrapings from 76 families, including mother, father, and infant, and semen samples were collected over 2 years of follow-up, analyzed by nested PCR, and confirmed by hybridization with 12 high-risk (HR) HPV types. The most common HPV profile was HR HPV in all family members (29%), followed by HPV-positive mother-infant pairs (26%). HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
3
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 28 publications
5
204
3
7
Order By: Relevance
“…Studies have demonstrated that oral infection by HPV is not uncommon [3,9]. However, evidence suggests that virtually all immune competent patients clear the viral infections [10][11][12][13], supporting the hypothesis that most individuals experience only transient infection.…”
Section: Introductionmentioning
confidence: 92%
“…Studies have demonstrated that oral infection by HPV is not uncommon [3,9]. However, evidence suggests that virtually all immune competent patients clear the viral infections [10][11][12][13], supporting the hypothesis that most individuals experience only transient infection.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, in two independent studies, HPV 16 has been found to be present in breast tumours that occur in European women with HPV 16-associated cervical cancer (Hennig et al, 1999;Widschwendter et al, 2004). Virions (virus particles) are shed from desquamating keratinocytes (the target cells for HPV infections) and high-risk HPVs can be transmitted by close human nonsexual contact (Bryan and Brown, 2001;Rintala et al, 2005). Accordingly, we speculate that HPVs may be transmitted by hand from the female perineum to the breast which could occur, for example, during showering or bathing.…”
Section: ----------------------------C------------------------------4mentioning
confidence: 99%
“…Peripartum vertical transmission of HPV infection to infants has been reported. 33 However, although the incidence of cervical cancer is higher in South than in North America because of differences in screening practices, HPV infection prevalence is quite similar. We consider it less likely that the behavior of these viruses would differ by geography; however, we cannot entirely exclude the possibility of a critical cofactor (e.g.…”
mentioning
confidence: 99%